Uniform-graded mesh block method for second kind Volterra integral equations - Attia, Gamal M. (Computer Assisted Methods in Engineering and Science, 1998)
In this paper a block method is developed to use on uniform-graded mesh for the solution of Volterra integral equations of the second kind. This method permits the use of a variable step size when solving Volterra integral equations. Means of reducing the error. Extensive results are presented.